Evaluación del uso de ECEGON® en un protocolo de IATF en ovinos - Bruno Galarraga, María Macarena; Fernandez, Jimena; Correa, A.; Rodriguez Persico, Juan Manuel; Qarih, Fahd; Cueto, Marcela Isabel; Gibbons, Alejandro Eduardo (Asociación Argentina de Producción Animal, 2022)
Poster